2019
DOI: 10.1186/s13075-019-1903-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance of 18F-sodium fluoride positron emission tomography with computed tomography to assess inflammatory and structural sacroiliitis on magnetic resonance imaging and computed tomography, respectively, in axial spondyloarthritis

Abstract: Purpose To assess increased sacroiliac joint (SIJ) uptake on 18 F-NaF PET/CT and to compare with MRI for inflammation and with CT scan for structural damages in a population of 23 patients with spondyloarthritis (SpA). Methods Twenty-three patients with active SpA according to the Assessment of SpondyloArthritis international Society (ASAS) and/or modified NY criteria were included. All patients had a pelvic radiograph, MRI, and CT scan of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…Examples of other applications include combining CT with positron emission tomography (PET). PET/CT using 2-deoxy-2[18F]fluoro-d-glucose (FDG) to visualize glucose metabolism has been has recently been used to investigate increased glycolysis due to inflammation in inflammatory arthritis, demonstrating correlations between metabolic markers identified with PET and clinical diseases activity in rheumatoid arthritis ( 44 ), and between PET activity score and inflammation score on MRI in patients with sacroiliitis in spondylarthropathy ( 45 ). Further, PET uptake predicts radiographic progression in RA ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of other applications include combining CT with positron emission tomography (PET). PET/CT using 2-deoxy-2[18F]fluoro-d-glucose (FDG) to visualize glucose metabolism has been has recently been used to investigate increased glycolysis due to inflammation in inflammatory arthritis, demonstrating correlations between metabolic markers identified with PET and clinical diseases activity in rheumatoid arthritis ( 44 ), and between PET activity score and inflammation score on MRI in patients with sacroiliitis in spondylarthropathy ( 45 ). Further, PET uptake predicts radiographic progression in RA ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown a moderate correlation between 18 F-fluoride uptake on PET-MRI and BME in the SIJ (kappa= 0.64) and a poor correlation in the spine (kappa=0.25) [121]. Overall, the correlation between osteoblastic activity on PET and BME is still controversial, especially in the spine [119,122]. Concerning structural lesions, no correlation was found between 18 F-fluoride PET and the presence of erosions, ankylosis, and sclerosis visible on the SIJ CT scans [119].…”
Section: Diagnostic Performance Of 18 F-fluoride Pet Scanmentioning
confidence: 99%
“…Positron emission tomography (PET) is a nuclear imaging technique that can be used as hybrid imaging when combined with CT or MRI for anatomical reference. Similarly to MRI, PET may be useful in the early diagnosis of axSpA since it may allow early detection of inflammatory changes even before structural damage occurs [119]. It can visualize and quantify disease activity at different targeted binding sites in the whole body (bone marrow, synovial tissue, ligament, and entheses) through the use of different specific tissue tracers.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Since the syndesmophyte formation is not clearly identifiable on MRI, new techniques dedicated to bone remodelling, such as PET-CT, may play a role [57]. In recent years, the PET diagnostic potential has been considered in both infectious and inflammatory diseases, such as polymyalgia rheumatica, vasculitis, and rheumatoid arthritis [58].…”
Section: Fna 18 Pet Ctmentioning
confidence: 99%